Non-enzymatic recombination of RNA: Ligation in loops - Staroseletz, Yaroslav; Nechaev, Sergey; Bichenkova, Elena; Bryce, Richard A.; Watson, Catherine; Vlassov, Valentin; Zenkova, Marina (Biochimica et biophysica acta, 2018)
While the RNA world hypothesis is widely accepted, it is still far from complete: the existence of self-replicating ribozyme, consisting of potentially hundreds of nucleotides, is a core assumption for the majority of RNA world models. The appearance of such long RNA molecules under prebiotic conditions is not self-evident. Recombination seems to be a plausible way of creating RNA diversity, resulting in the appearance of functional RNAs, capable of self-replicating. We report here on the study of recombination process modelled with two 96 nts RNA fragments. Detection of recombination products was performed with RT-PCR followed by TA-cloning and Sanger sequencing. A wide range of recombinant products was detected. We found that (i) the most efficient ligation was observed for RNA species forming bulges or internal loops, with ligation partners located within the loop; (ii) a strong preference was observed for formation of a few types of major products with a large variety of minor products; (iii) ligation could occur with participation of either 2′,3′-cyclophosphate or 5′-ppp; (iv) the presence of key reaction components, i.e. 5′ppp-RNAs, enabled the formation of additional types of product; (v) molecular dynamics simulations of one of the most abundant products suggests that the ligation results in a preferable formation of 2′-5′- rather than 3′-5′-linkages. The study demonstrates regularities of new RNA molecules formation with non-enzymatic recombination process. Our findings provide new data supporting the RNA World hypothesis and show the way of new RNA sequences emergence under prebiotic conditions. [Display omitted] •Cell-free RNA recombination results in formation of wide range of products.•Ligation could occur with participation of either 2′,3′-cyclophosphate or 5′-ppp as activated form of substrate.•Molecular dynamics simulations suggest a preferable formation of 2′-5′- rather than 3′-5′-linkages.